A prospective study of association of cancer stem cell marker aldehyde dehydrogenase 1 with clinicopathological profile in lung carcinoma patients - Neema Tiwari; Anand N Srivastava; Nishi Tandon; Nirupma Lal; Shailendra Yadav; Surya Kant; Manoj Jain (Wolters Kluwer Medknow Publications, 2018)
Context: In India, lung carcinoma is the fifth-most common tumor and second-most common tumor in the males as per the Indian Council of Medical Research registry of 2002. It has been seen that ALDH1 expression in non-small cell lung cancer (NSCLC) and the presence of marker was linked to a more tumorigenic potential in the in vivo assessment and shorter disease-free survival in NSCLC patients with platinum treatment. Aims: Hence, our objective was to detect association of cancer stem cell (CSC) marker aldehyde dehydrogenase 1 (ALDH1) with clinicopathological profile in lung carcinoma patients. Settings and Design: This is a Pilot study. Subjects and Methods: It was a Pilot study where biopsies from 55 fresh previously untreated lung cancer patients visiting the Pulmonary Medicine Department of Era's Lucknow Medical College and Hospital Lucknow and King George's Medical University were taken for 18 months November 2014-April 2016, after taking proper informed consent from them. Paraffin blocks were taken and stained by hematoxylin and eosin (Sigma) to make the histopathological diagnosis and immunohistochemistry was done for detection of CSC marker ALDH1 (Daco). Statistical Analysis Used: The statistical analysis was done using Statistical Package for Social Sciences Version 15.0 Statistical Analysis Software. The values were represented in number (%) and mean ± standard deviation. Results: Expression of stem cell marker ALDH1 with the staging of the tumor was observed in 62.5% of Stage I, 80% of Stage II, 94.1% of Stage III, and 100% of Stage IV cases. Statistically, there was a significant association between ALDH1expression and stage of disease (P < 0.001). Diagnostic efficacy of ALDH1 expression in the detection of any positive clinical stage, it was found to be 88.6% sensitive and 90.9% specific. Conclusions: Strong ALDH1 expression correlates with higher stage of lung carcinoma making it a prognostic marker needing in-depth study.